Principalele etape în evoluţia conceptului "realizarea dreptului" [Articol] - Cuznețov, Alexandru; Avornic, Gheorghe (My University, 2009)
Law is a complex outcome of the society, taking this into regard, law comes up like a inseparable dimension of the social existence. The existence and realization of law is one of the compulsory conditions of public order. Order constitutes the main condition of social cohesion, being determined by the existence of normative systems and mechanisms of bringing into life their content. The present article analyzes the main periods in the evolution of the concept of “realization of law” as the main social guarantee.